1996
DOI: 10.1046/j.1365-2141.1996.7442370.x
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell yield in sequential blood stem cell mobilization in the same patients: insights into chemotherapy dose escalation and combination of haemopoietic growth factor and chemotherapy

Abstract: Between April 1988 and March 1994 a total of 23 patients with haematological or non-haematological malignancies received serial peripheral blood stem cell (PBSC) mobilization to attain sufficient harvest for PBSC transplant at our institution. There was no improvement in yield with the second mobilization for group A patients (n = 12) who had the same dose of cyclophosphamide twice as mobilizing agent. For group B patients (n = 6). who had a higher dose of cyclophosphamide with the second mobilization, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…We have previously shown that remobilization using the same mobilization stimulus within 3 months produced progenitor yields not different from the initial mobilization. 12 While it is not ethical to repeat mobilization procedures in patients who have sufficient stem cells for transplantation, repeat mobilization studies may be done in patients who fail to mobilize sufficient cells for transplantation. 13 This design would avoid the confounding effect of interpatient differences and tests rHuSCF's efficacy by comparing the mobilization yield with and without rHuSCF in the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that remobilization using the same mobilization stimulus within 3 months produced progenitor yields not different from the initial mobilization. 12 While it is not ethical to repeat mobilization procedures in patients who have sufficient stem cells for transplantation, repeat mobilization studies may be done in patients who fail to mobilize sufficient cells for transplantation. 13 This design would avoid the confounding effect of interpatient differences and tests rHuSCF's efficacy by comparing the mobilization yield with and without rHuSCF in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…Leukaphereses were performed on a Fenwal CS3000 plus (Baxter, Deerfield, IL, USA) as described before 1,12 and were continued until a maximum of four procedures were performed or until a target of X3 Â 10 6 CD34 + cells/kg was reached. Separate pilot tubes were cryopreserved for laboratory studies.…”
Section: Rationale For Study Designmentioning
confidence: 99%
“…Lie et al 12 recently evaluated several remobilization strategies for individual patients who mobilized poorly. Using CFU-GM as the marker for stem cell yields, they demonstrated that, for patients initially mobilized with cyclophosphamide alone, the same chemotherapy dose yielded the same CFU-GM dose/kg for the first and second mobilizations (23.0 vs 15.4 × 10 4 CFU-GM/kg).…”
Section: Remobilizationmentioning
confidence: 99%
“…12,13 For instance, if patients are mobilized with cytokines alone, mobilization should not occur until 4-5 weeks after chemotherapy has been completed. If mobilization is performed too early and the yield is poor, a second mobilization with the same regimen may be of value.…”
Section: Remobilizationmentioning
confidence: 99%
“…3,5 With the advent of hematopoietic growth factors (HGF), the use of combined chemotherapy and HGF in mobilizing PBSC results in a shorter cytopenic phase, reduction of infection risks and duration of hospital stay and enhances PBSC yield compared to mobilization with chemotherapy alone. 4,[6][7][8][9][10] Nevertheless, the dosages and scheduling of chemotherapy and HGF to optimize the cell yield, and hence the successful outcome of mobilization, remain to be studied. …”
mentioning
confidence: 99%